The Effect of Adding Various Levels of Bokashi from Gliricidia Leaves and Goat Faeces on the Growth, Production and Chemical Composition of Arbila’s (Phaseolus lunatusL.) Forage - Bernadete Barek Koten; Redempta Wea; Rosalin Kana Tiry; Seni Otto; Apriana Wasti Belandina Selan; Welius Yikwa; Allan Prima Titong (Buletin Peternakan, 2022)
This study aimed to evaluate the effect of adding various levels of bokashi from gliricidia leaves and goat faeces on the growth, production and chemical composition of arbila's forage, has been carried out for 5 months, was designed with completely randomized, 4 treatments with 5 replications, consisting of P0: without bokashi, P5: 5 tons bokashi/ha, P10: 10 tons bokashi/ha, and P15: 15 tons bokashi/ha. Variables measured were number of root nodules, percentage of effective nodules, nitrogen uptake, stem diameter, increase in number of leaves, stem and leaf ratio, forage production (fresh, dry matter (DM), organic matter (OM) and crude protein (CP), and chemical composition. Data were analyzed by variance analysis and followed by Duncan's test. Result of the research, the treatment had a very significant effect (P<0.01) on the increase number of leaves, OM dan CP forage productions. Futhermore, had a significant effect (P<0.05) on the number of root nodules, nitrogen uptake, stem diameter, fresh and DM forage productions, content of DM, OM, CP, crude fiber (CF), nitrogen free extract (NFE), and ash, but did not affect on percentage of effective nodules, stem and leaf ratio, and extract ether (EE) content of forage. Duncan's test showed that the P15 produced the highest number of root nodules, N uptake, leaf growth, fresh, DM, OM and CP production, and the content of OM, CP, NFE in arbila's forage. It was concluded that this bokashi can improve the growth, production and chemical composition of arbila's forage and the best level is 15 tons bokashi/ha.